Digitalisation and decarbonisation challenges of inland waterways freight logistics transport and their integration into regional supply chains - Shekwoyemi, Gbako (Logistics, supply chain, sustainability and global challenges, 2023)
An era of increased sustainable transport, the European inland navigation industry has received significant attention to attain sustainable transport. Tremendous opportunities to substantially move freight on waterways are present in the UK; however, several challenges have been appropriately addressed, including infrastructural gaps and various institutional support programs. The paper addresses the UK's current situation of inland navigation and the key challenges affecting the sectors as a viable alternative transport solution. The article explores and summarises the geographic opportunities, commercial feasibility, and the current condition of the UK'S inland navigation sector. From the practical scenario of the UK's experience, an attempt was made by the authors to find the critical challenges and issues faced by the industry. The emerging themes from the analysis of this paper indicated governance and leadership issues, cooperation, and coordination mechanism between establishments with various functions and responsibilities, merged with infrastructural investment, are strategic elements for expansion in the UK. Conclusively, the authors presented recommendations for improvement and sustainable development.
Keywords: challenges; decarbonisation; digitalisation; digitalizacija,; infrastruktura plovnih poti; inland waterway transport; intermodal transport; intermodalni promet; investments; izzivi; modal shift; modalni premik; naložbe; promet po celinskih plovnih poteh; razogljičenje; sustainable development; trajnostni razvoj; waterway infrastructure